Managers of the Russian Firms: Overestimated Self-Assessment or Success Self-Convincement - ПеникасГенрих Иозович (Journal of Economic Sociology, 2010)
Within the framework of the study on the assessment of industrial firms’ competitiveness in Russia we found out that the level of competitiveness is determined by different factors from those that were described by the managers. It was shown that sometimes the managers implement the strategies expecting the growth of competitiveness but this implementation does not lead to the real competitiveness growth what leads to the difference in objective and subjective assessment of firms’ competitiveness. The paper provides the discussion of the reasons for this difference on the basis of the analysis of factors and economic peculiarity of some industries.